2016
DOI: 10.1111/nph.13970
|View full text |Cite
|
Sign up to set email alerts
|

Plants adapted to nutrient limitation allocate less biomass into stems in an arid‐hot grassland

Abstract: SummaryBiomass allocation can exert a great influence on plant resource acquisition and nutrient use. However, the role of biomass allocation strategies in shaping plant community composition under nutrient limitations remains poorly addressed.We hypothesized that species-specific allocation strategies can affect plant adaptation to nutrient limitations, resulting in species turnover and changes in community-level biomass allocations across nutrient gradients. In this study, we measured species abundance and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 59 publications
(73 reference statements)
1
47
0
Order By: Relevance
“…These allocations are consistent with those in other epiphytes and terrestrial plants (Zhang et al, ; Zotz, ). The increased allocation of nutrients to the leaves might be an adaptation to a nutrient‐limited environment (Yan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These allocations are consistent with those in other epiphytes and terrestrial plants (Zhang et al, ; Zotz, ). The increased allocation of nutrients to the leaves might be an adaptation to a nutrient‐limited environment (Yan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Between plant organs, the scaling relationship of N and P differs between primarily structural organs (stems and roots) and metabolically active leaves (Kerkhoff et al, 2006). In an arid and hot grassland, plants allocate more resources to leaves than to stems for adaptations to the nutrient-limited environment (Yan et al, 2016). The stoichiometry is different among different functional groups of terrestrial plants, including between herbaceous and woody plants (Kerkhoff et al, 2006;Tian et al, 2018), deciduous and evergreen plants (Aerts & Chapin, 1999;Güsewell, 2004), gymnosperms and angiosperms (Sardans et al, 2016), and among herbs, shrubs, and trees (Han, Fang, Guo, & Zhang, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to the optimal partitioning theory, plants usually allocate relatively more biomass to shoots if the limiting factors for growth are above the ground (e.g., CO 2 and sunlight) and more biomass to roots if the limiting factors are below the ground (e.g., water and nutrients). Thus, in order to realize optimal growth, plants will allocate biomass preferentially to the organ that accesses the most growth-limiting resources (Yan et al, 2016). Several studies have reported that plants in desert ecosystems have a larger root/shoot ratio (R/S) than plants in other ecosystems, such as forest and steppe ecosystems (Scheck and Jackson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in nitrogen dilution curves for wheat has been reported that relates to phenological development, hence the attempts to model critical nitrogen against phenological stage ( Angus, 2007 ; Yue et al, 2012 ; Zhao et al, 2014 ; Ratjen and Kage, 2016 ). Variation in allometric relations, between organs as well as between structural and labile carbohydrates, partially underlies the effect of phenology on nitrogen dilution curves ( Gastal et al, 2015 ; Hoogmoed and Sadras, 2016 ; Yan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%